The Imitation in the Paintings of Nineveh’s Artists (Al-Academy, 2025)
This research, titled (The Imitation in the Paintings of Nineveh’s Artists), tackles study Nineveh’s Artists works, especially those of the city of Mosul, who tried to imitate the reality of the city with its different parts. The research consists of four chapters. Chapter One deals with the type of the problem and sets the objectives to know the essence and types of this imitation to reach the desired results. The chapter also contains the importance of the research, its limits, and the delineation of the terms.Chapter Two contains the theoretical framework on two topics; the first is under the title civilization, the heritage, and the nature of Mosul city. The second section came under the title the reflection of the reality of Mosul in its artists’ paintings. Mosul is the focus of the subject in polarizing the hands of the artists towards it’s nature and heritage. The chapter then includes the indicators of the theoretical framework and literature. Chapter Three focuses on the methodology followed in the research, which is the descriptive analytical method. Then the research moves to the research community that included the works of the artists who tried to imitate the city through its different angles and subjects. The artists are Rakan Dabdoub, Najeeb Younis, Dherar Qaddo, Basheer Taha, Nabeel Saleh, and others. The chapter introduces also the tool and subjects of the research based on the intentional method analyzed in the light of the methodology adopted to reach the results that realize the objectives of the research referred to in Chapter Four.Chapter Four shows how the artist in an intentional way or another depicts Mosul solely in a special style sticking to one type of imitation:Simple imitation, which we notice in the works of Nabeel Saleh that imitate the reality of the houses of Mosul.Imitation of the essence which we touched in the works of Basheer Taha that trace the elements of nature that affect them.Imitation of the essence of traditions and customs in the works of Najeeb Younis.The imitation of Dherar Qaddo is a transition from the simple to the essence in the structure of modernistic formation.The researcher reached conclusions, recommendations, and suggestions, followed by a list of resources, references and appendices.